Mitigation of He embrittlement and swelling in nickel by dispersed SiC nanoparticles. (15th January 2016) - Huang, H.F.; Zhang, W.; De Los Reyes, M.; Zhou, X.L.; Yang, C.; Xie, R.; Zhou, X.T.; Huai, P.; Xu, H.J.
Abstract: The development of high-temperature irradiation-resistant nickel-based alloys has been receiving much attention due to their potential applications in molten salt reactors (MSRs). Pure nickel and SiC nanoparticles dispersed nickel-based alloys (Ni–SiCNP composites) have been characterized by transmission electron microscopy (TEM) to determine the helium diffusion behavior under 3 MeV helium ion irradiation at 600 °C with ion fluence up to 3 × 10 20 ions/m 2 . The TEM results indicated that the presence of dispersed SiCNP in nickel can inhibit the growth of helium bubbles, thereby mitigate the helium embrittlement and swelling of nickel-based alloys. The theoretical calculation results using the density functional theory (DFT) showed that the helium atoms prefer to diffuse to the interface between SiCNP and nickel matrix, and thus avoid the grain boundary segregation and also the growth of helium bubbles. This study confirmed the feasibility of dispersing carbides in nickel-based alloys to improve the irradiation-resistant performance of materials. Graphical Abstract: Highlights: Ni–SiCNP composite has been prepared by a Powder Metallurgy Route. DFT calculation showed that helium tends to be absorbed by the interfaces between matrix and SiCNP . Dispersed SiCNP mitigates the helium embrittlement and swelling on nickel. The feasibility of dispersed SiCNP for improving the radiation-resistant performance of nickel based alloys was confirmed.